Composite polyanionic positive electrode material and preparation method thereof

CN122992059APending Publication Date: 2026-10-27ZHEJIANG JUSI CHUANGNENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611476819.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

若将磷酸钛锰钠/碳材料与磷酸焦磷酸铁钠/碳材料简单机械干混,不同颗粒之间接触有限,难以形成稳定复合二次颗粒,对压实密度和容量发挥的改善有限

Benefits of technology

[0020]1、本复合聚阴离子正极材料通过结构设计,内层的磷酸钛锰钠/碳为正极材料提供容量贡献,使复合聚阴离子正极材料具有较高可逆容量。外层的磷酸焦磷酸铁钠/碳具有稳定聚阴离子骨架,可改善颗粒表面稳定性和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992059A_ABST
    Figure CN122992059A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite polyanion positive electrode material and preparation method thereof, comprising: inner layer and outer layer, inner layer includes sodium titanium manganese phosphate / carbon material, outer layer includes sodium iron pyrophosphate / carbon material, and outer layer is coated, half-coated or composite distribution in the outside of inner layer, wherein, sodium titanium manganese phosphate / carbon material is obtained by solid phase method once sintering, provides reversible capacity space and exists as particle skeleton;Sodium iron pyrophosphate / carbon material is in the form of slurry with sodium titanium manganese phosphate / carbon material and is sintered twice to obtain composite polyanion positive electrode material, and carbon network is formed by carbon source pyrolysis after twice sintering, improve material electronic conductivity and rate performance.The composite polyanion positive electrode material is designed by structure and combined with secondary sintering process, and the positive electrode material obtained by detection significantly improves electronic conductivity and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery cathode material technology, specifically to a composite polyanionic cathode material and its preparation method. Background Technology

[0002] Sodium-ion batteries are considered an important electrochemical energy storage system for large-scale energy storage, low-speed power, and backup power due to the abundance and wide distribution of sodium resources, low cost, and good safety. Polyanionic cathode materials have advantages such as structural stability, good thermal stability, and long cycle life, making them an important direction for sodium-ion battery cathode materials.

[0003] Sodium titanium manganese phosphate (SMT) materials exhibit high capacity potential and good structural stability. Manganese provides the main electrochemical capacity, while titanium helps stabilize the polyanionic framework. However, conventional solid-state methods for preparing SMT materials still have room for improvement in terms of particle density, compaction density, and interfacial stability. Furthermore, the intrinsic electronic conductivity of the phosphate system is relatively low, necessitating carbon coating or composite structures to improve conductivity.

[0004] Sodium iron pyrophosphate can be considered as a combination of NaFePO4 and Na2FeP2O7, which has the characteristics of low cost, stable structure and good cycle performance. However, its capacity and energy density are still limited when used alone as a cathode material. If sodium titanium manganese phosphate / carbon material is simply mechanically dry-mixed with sodium iron pyrophosphate / carbon material, the contact between different particles is limited, making it difficult to form stable composite secondary particles, and thus the improvement on compaction density and capacity is limited.

[0005] Therefore, it is necessary to provide a new composite structure and process that uses sodium titanium manganese phosphate / carbon material as a high-capacity inner layer and sodium iron phosphate pyrophosphate / carbon material as a stable outer layer, and forms tightly bonded composite particles through a special preparation process, thereby simultaneously improving capacity, compaction density and cycle stability. Summary of the Invention

[0006] This invention provides a composite polyanionic cathode material and its preparation method. The material uses an inner layer of sodium manganese titanium phosphate / carbon to provide the main capacity contribution, and an outer layer of sodium iron pyrophosphate / carbon to improve particle surface stability and processing compaction performance, thereby simultaneously improving capacity, compaction density and cycle stability.

[0007] This invention provides the following technical solution: a composite polyanion cathode material, comprising: an inner layer and an outer layer, wherein the inner layer comprises sodium titanium manganese phosphate / carbon material, and the outer layer comprises sodium iron phosphate pyrophosphate / carbon material, and the outer layer is coated, partially coated, or compositely distributed on the outside of the inner layer, wherein the sodium titanium manganese phosphate / carbon material is obtained by solid-state sintering in one step, providing reversible capacity space and existing as a particle skeleton; the sodium iron phosphate pyrophosphate / carbon material is composited with the sodium titanium manganese phosphate / carbon material in slurry form and sintered in two steps to obtain the composite polyanion cathode material, and after the two sinterings, the carbon source is pyrolyzed to form a carbon network, thereby improving the electronic conductivity and rate performance of the material.

[0008] The inner layer of this composite polyanionic cathode material provides the main capacity and serves as the particle framework. The outer layer is formed by secondary sintering at 500°C to 600°C, which stabilizes the surface, improves density and compaction, and the carbon network formed by the pyrolysis of the carbon source during the two sintering processes improves electronic conductivity and rate performance.

[0009] As an alternative embodiment of the composite polyanionic cathode material described in this invention, the chemical formula of sodium titanium manganese phosphate is Na. x Mn y Ti z M n (PO4)3, where M is the dopant element, 1≤y≤1.2, 0≤n≤0.5, y+z+n=2, and x is the number of moles of sodium element that satisfy the charge balance of the chemical formula; M is Li + K + Mg 2+ Ca 2+ 、Sr 2+ Zn 2+ Co 2+ Ni 2+ Cu 2+ Al 3+ Cr 3+ Fe 3 + V 3+ Y 3+ La 3+ Ga 3+ Sn 4+ Zr 4+ 、Nb 5+ W 6+One or more combinations of the following. Sodium iron pyrophosphate includes NaFePO4 and Na2FeP2O7, with a molar ratio of NaFePO4 to Na2FeP2O7 of 1-2:1. When the molar ratio is 2:1, the combination composition corresponds to Na4Fe3(PO4)2(P2O7). The outer layer of sodium iron pyrophosphate is not doped with metal elements to keep the outer layer composition simple, reduce costs, and avoid complicating the outer layer phase composition. After the sodium iron pyrophosphate / carbon material is combined with sodium titanium manganese phosphate / carbon material in slurry form, the mass ratio of sodium titanium manganese phosphate / carbon to sodium iron pyrophosphate / carbon is 50:50 to 95:5. The carbon content in the composite polyanionic cathode material is 0.5wt% to 8wt%, and the composite polyanionic cathode material is spherical or near-spherical secondary particles with a D50 of 3μm to 20μm.

[0010] A method for preparing a composite polyanionic cathode material includes:

[0011] S1. Sodium source, manganese source, titanium source, phosphorus source and carbon source are mixed and solid-state sintered to obtain sodium titanium manganese phosphate / carbon material, wherein the solid-state sintering temperature is 500℃ to 750℃.

[0012] S2. Add sodium source, iron source, phosphorus source, pyrophosphate source and carbon source to the liquid phase, grind or disperse to obtain sodium iron pyrophosphate / carbon precursor slurry, wherein the iron source is selected from one or more of ferrous oxalate, ferric phosphate, ferric oxide, ferric nitrate and ferric acetate; the phosphorus source is selected from one or more of phosphoric acid, sodium dihydrogen phosphate, sodium pyrophosphate, pyrophosphate and ammonium pyrophosphate.

[0013] S3. Add the sodium titanium manganese phosphate / carbon material obtained in step S1 to the sodium iron phosphate pyrophosphate / carbon precursor slurry obtained in step S2, mix evenly to obtain a composite slurry, and then continue to stir, sand mill, ball mill or high speed dispersion for 10 min to 180 min.

[0014] S4. Spray dry the composite slurry to obtain composite precursor particles, wherein the inlet air temperature of the spray dryer is 160℃ to 260℃, the outlet air temperature is 80℃ to 130℃, and the solid content of the composite slurry is 20wt% to 60wt%.

[0015] S5. The composite precursor particles are sintered at 500°C to 600°C to obtain a composite polyanion cathode material. The holding time for the second sintering is 2h to 12h, and the sintering atmosphere is nitrogen, argon or a nitrogen-hydrogen mixture.

[0016] The preparation method of this composite polyanionic cathode material differs from simple dry mixing. By introducing sodium titanium manganese phosphate / carbon material into the outer precursor slurry stage, the outer precursor components can adhere to, coat, or be compositely distributed on the surface of the inner particles. After spray drying, spherical or near-spherical composite precursors are formed. Secondary sintering at 500℃ to 600℃ causes the outer sodium iron phosphate pyrophosphate / carbon phase to form in situ, which is equivalent to a secondary heat treatment of the sodium titanium manganese phosphate / carbon inner layer, thus improving particle compaction and compaction density.

[0017] A sodium-ion battery cathode material comprising the aforementioned composite polyanionic cathode material.

[0018] A sodium-ion battery, comprising the aforementioned sodium-ion battery positive electrode.

[0019] The present invention has the following beneficial effects:

[0020] 1. Through structural design, the inner layer of this composite polyanion cathode material, sodium manganese titanium phosphate / carbon, contributes to the cathode material's capacity, resulting in a high reversible capacity. The outer layer, sodium iron pyrophosphate / carbon, provides a stable polyanion framework, improving particle surface stability and cycle performance.

[0021] 2. The preparation process of this composite polyanionic cathode material involves wet compounding and spray drying to form spherical or near-spherical composite secondary particles, improving powder flowability and electrode processing performance. Secondary sintering at 500℃ to 600℃ is equivalent to a second sintering treatment of the sodium manganese titanium phosphate / carbon inner layer, which is beneficial for further particle densification, thereby increasing compaction density. The inner and outer carbon layers form a composite conductive network, improving the material's electronic conductivity and rate performance. This process uses conventional equipment such as solid-phase sintering, liquid-phase grinding, spray drying, and atmosphere sintering, making it suitable for industrial-scale production. Attached Figure Description

[0022] Figure 1 The charge-discharge curves of the composite polyanion cathode material in Example 1 of this invention are shown.

[0023] Figure 2 The charge-discharge curves of the composite polyanion cathode material in Example 2 of this invention are shown.

[0024] Figure 3 The charge-discharge curves of the composite polyanion cathode material in Example 3 of this invention are shown.

[0025] Figure 4 The charge-discharge curves of the composite polyanion cathode material in Example 4 of this invention are shown. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Example 1

[0028] Sodium carbonate, manganese carbonate, titanium dioxide, and ammonium dihydrogen phosphate were weighed according to a Na:Mn:Ti:P molar ratio of 3.15:1.05:0.95:3.00. Glucose was added as a carbon source, with the amount of glucose added being 6 wt% of the theoretical product mass. The above raw materials were ball-milled or sand-milled and then dried. After drying, the mixture was placed in a nitrogen atmosphere and sintered at 650°C for 10 h. After cooling, the mixture was crushed and sieved to obtain sodium titanium manganese phosphate / carbon material.

[0029] Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, and sodium pyrophosphate were weighed according to a 2:1 molar ratio of NaFePO4 to Na2FeP2O7. Glucose and deionized water were added, and the mixture was dispersed by sand milling to obtain a sodium iron pyrophosphate / carbon precursor slurry. This composition corresponds to Na4Fe3(PO4)2(P2O7). The solid content of the slurry was controlled between 35wt% and 45wt%, and the D50 of the solid particles in the slurry after sand milling was 200nm to 1000nm.

[0030] The obtained sodium titanium manganese phosphate / carbon material was added to the sodium iron phosphate pyrophosphate / carbon precursor slurry, wherein the mass ratio of the sodium titanium manganese phosphate / carbon material to the theoretical product of sodium iron phosphate pyrophosphate / carbon was 8:1. Stirring or milling was continued for 30 to 90 minutes to ensure that the outer precursor components were uniformly adhered to or distributed on the surface of the sodium titanium manganese phosphate / carbon particles, thus obtaining the composite slurry.

[0031] The composite slurry is spray-dried at an inlet air temperature of 220°C and an outlet air temperature of 105°C to obtain spherical or near-spherical composite precursor particles.

[0032] The composite precursor particles were placed in a nitrogen atmosphere and sintered twice at 550℃ for 10 h, causing the sodium iron phosphate pyrophosphate / carbon phase to form on the outside of the sodium titanium manganese phosphate / carbon particles, while the inner layer of the sodium titanium manganese phosphate / carbon underwent a second heat treatment to densify it. After cooling, the particles were lightly crushed and sieved to obtain the sodium titanium manganese phosphate / carbon-sodium iron phosphate pyrophosphate / carbon composite polyanionic cathode material.

[0033] Example 2

[0034] The difference between this embodiment and Example 1 is that the mass ratio of the sodium manganese titanium phosphate / carbon material to the theoretical product of sodium iron phosphate pyrophosphate / carbon is 7:1, while the remaining steps are the same as in Example 1. The resulting material exhibits an increased sodium iron phosphate pyrophosphate / carbon ratio in the outer layer, further improving surface stability and cycle performance, making it suitable for long-cycle sodium-ion batteries.

[0035] Example 3

[0036] The difference between this embodiment and Example 1 is that the mass ratio of the sodium titanium manganese phosphate / carbon material to the theoretical product sodium iron phosphate pyrophosphate / carbon is 9:1, while the remaining steps are the same as in Example 1. The resulting material has a higher proportion of the high-energy-density sodium titanium manganese phosphate / carbon inner layer, while a small amount of sodium iron phosphate pyrophosphate / carbon outer layer improves the particle surface condition and secondary sintering densification effect, making it suitable for cathode material systems with high energy density requirements.

[0037] Example 4

[0038] The difference between this embodiment and Example 1 is that the sodium iron pyrophosphate / carbon precursor slurry is prepared by combining NaFePO4 and Na2FeP2O7 in a 1:1 molar ratio, and no metal dopant sources other than sodium, iron, phosphorus, pyrophosphate, and carbon are added. The remaining steps are the same as in Example 1, resulting in a composite cathode material with an outer layer of NaFePO4 and Na2FeP2O7.

[0039] Example 5

[0040] The difference between this embodiment and Embodiment 1 is that the molecular formula of sodium titanium manganese phosphate is Na. 3.2 Mn 1.1 Ti 0.9 (PO4)3, sodium carbonate, manganese carbonate, titanium dioxide and ammonium dihydrogen phosphate are weighed according to the molar ratio of Na:Mn:Ti:P of 3.25:1.10:0.9:3.00.

[0041] Comparative Example 1

[0042] In this embodiment, the two finished materials are simply dry-mixed. Specifically, sodium titanium manganese phosphate / carbon material and sodium iron pyrophosphate / carbon material are prepared separately and then mechanically dry-mixed at a mass ratio of 8:1, without outer layer precursor slurry composite, spray drying, or secondary sintering at 500°C to 600°C. This comparative example is used to illustrate that simple dry mixing is difficult to form a stable inner and outer layer composite structure, and the effect of particle contact and compaction improvement is limited.

[0043] The difference between Comparative Example 2 and Example 1 is that the ratio of sodium titanium manganese phosphate to sodium iron pyrophosphate is 97:3.

[0044] The difference between Comparative Example 3 and Example 1 is that the ratio of sodium titanium manganese phosphate to sodium iron pyrophosphate is 4:6.

[0045] The difference between Comparative Example 4 and Example 1 is that the molecular formula of sodium titanium manganese phosphate is Na. 2.8 Mn 0.9 Ti 1.1 (PO4)3, sodium carbonate, manganese carbonate, titanium dioxide and ammonium dihydrogen phosphate are weighed according to the molar ratio of Na:Mn:Ti:P of 2.85:0.90:1.10:3.00.

[0046] Electrochemical performance was tested using a coin cell, with a sodium anode, a cathode made of the same material, a glass fiber separator, and a 1M NaClO4 in PC electrolyte. The cell model was 2032. The inner layer of sodium manganese titanium phosphate / carbon provides the main capacity, while the outer layer of sodium iron pyrophosphate / carbon improves interfacial stability and processing compaction. The composite material of this invention is expected to exhibit high reversible capacity, good rate performance, and stable cycle retention.

[0047] The test results of the above embodiments and comparative examples are shown in the table.

[0048] Table 1:

[0049]

[0050] Through Examples 1, 5, and Comparative Example 4, it can be concluded that the higher the manganese content in sodium titanium manganese phosphate, the higher the specific capacity of the material. Therefore, the Mn content in sodium titanium manganese phosphate is limited to 1-1.2.

[0051] As demonstrated in Example 1 and Comparative Example 1, the implementation of this patent is beneficial for improving the cyclic stability and compaction density of the material. The improved cyclic stability is mainly due to the higher stability of sodium iron pyrophosphate, which suppresses the side reactions of sodium titanium manganese phosphate. The improved compaction density is attributed to the fact that the core sodium titanium manganese phosphate is equivalent to sintering twice, promoting particle rearrangement.

[0052] Examples 1, 2, and 3, and Comparative Examples 2 and 3 illustrate that a high proportion of sodium titanium manganese phosphate helps to increase the voltage of the cathode material, thereby increasing the energy density of the material. Too low a proportion of sodium titanium manganese phosphate reduces the energy density, while too high a proportion leads to poor cycle life.

[0053] In summary, this invention employs solid-state sintering to prepare sodium titanium manganese phosphate / carbon materials, which are then wet-composite with sodium iron pyrophosphate / carbon precursor slurry. The composite polyanionic cathode material is prepared by spray drying and secondary sintering at 500°C to 600°C. The mixing, milling, spray drying, atmosphere sintering, crushing, and sieving processes involved can all be achieved using existing industrial equipment for battery cathode materials, demonstrating a strong foundation for large-scale production and significant application value.

[0054] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A composite polyanionic cathode material, characterized in that, It includes an inner layer and an outer layer. The inner layer consists of sodium titanium manganese phosphate / carbon material, and the outer layer consists of sodium iron pyrophosphate / carbon material. The outer layer is coated, partially coated, or compositely distributed on the outside of the inner layer. Among them, sodium titanium manganese phosphate / carbon material is obtained by solid-state sintering in one step, providing reversible capacity space and existing as a particle skeleton; sodium iron phosphate pyrophosphate / carbon material is compounded with sodium titanium manganese phosphate / carbon material in slurry form and sintered in two steps to obtain composite polyanion cathode material, and after the two sintering, the carbon source is pyrolyzed to form a carbon network, which improves the electronic conductivity and rate performance of the material.

2. The composite polyanionic cathode material according to claim 1, characterized in that: Sodium titanium manganese phosphate has the chemical formula Na. x Mn y Ti z M n (PO4)3, where M is the dopant element, 1≤y≤1.2, 0≤n≤0.5, y+z+n=2, and x is the number of moles of sodium that satisfy the charge balance of the chemical formula; M is Li + K + Mg 2+ Ca 2+ 、Sr 2+ Zn 2+ Co 2+ Ni 2+ Cu 2+ Al 3+ Cr 3+ Fe 3+ V 3+ Y 3+ La 3+ Ga 3+ Sn 4+ Zr 4+ 、Nb 5+ W 6+ One or more combinations of the above.

3. The composite polyanionic cathode material according to claim 1 or 2, characterized in that: Sodium iron pyrophosphate comprises NaFePO4 and Na2FeP2O7, with a molar ratio of 1-2:

1.

4. The composite polyanionic cathode material according to claim 1 or 2, characterized in that: When sodium iron pyrophosphate / carbon material is compounded with sodium titanium manganese phosphate / carbon material in slurry form, the mass ratio of sodium titanium manganese phosphate / carbon to sodium iron pyrophosphate / carbon is 50:50 to 95:

5.

5. The composite polyanionic cathode material according to claim 1 or 2, characterized in that: The carbon content in the composite polyanion cathode material is 0.5wt% to 8wt%, and the composite polyanion cathode material is spherical or near-spherical secondary particles with a D50 of 3μm to 20μm.

6. A method for preparing a composite polyanionic cathode material, used to prepare the composite polyanionic cathode material according to any one of claims 1-5, characterized in that, include: S1. Sodium source, manganese source, titanium source, phosphorus source and carbon source are mixed and sintered in solid phase to obtain sodium titanium manganese phosphate / carbon material; S2. Add sodium source, iron source, phosphorus source, pyrophosphate source and carbon source to the liquid phase, grind or disperse to obtain sodium iron pyrophosphate / carbon precursor slurry. S3. Add the sodium titanium manganese phosphate / carbon material obtained in step S1 to the sodium iron phosphate / carbon precursor slurry obtained in step S2, mix evenly, and obtain a composite slurry. S4. Spray dry the composite slurry to obtain composite precursor particles; S5. The composite precursor particles are sintered at 500°C to 600°C to obtain a composite polyanion cathode material.

7. The method for preparing the composite polyanionic cathode material according to claim 6, characterized in that: In step S1, the solid-state sintering temperature is successively from 500℃ to 750℃; After obtaining the composite slurry in step S3, continue stirring, sand milling, ball milling, or high-speed dispersion for 10 to 180 minutes; In step S4, the inlet air temperature for spray drying is 160°C to 260°C, the outlet air temperature is 80°C to 130°C, and the solid content of the composite slurry is 20wt% to 60wt%. The holding time for the second sintering in step S5 is 2 to 12 hours, and the sintering atmosphere is nitrogen, argon, or a nitrogen-hydrogen mixture.

8. The method for preparing the composite polyanionic cathode material according to claim 6, characterized in that: In step S2, the iron source is selected from one or more of ferrous oxalate, ferric phosphate, ferric oxide, ferric nitrate, and ferric acetate; the phosphorus source is selected from one or more of phosphoric acid, sodium dihydrogen phosphate, sodium pyrophosphate, pyrophosphate, and ammonium pyrophosphate.

9. A sodium-ion battery positive electrode, characterized in that: Includes the composite polyanionic cathode material as described in any one of claims 1 to 8.

10. A sodium-ion battery, characterized in that: Including the sodium-ion battery positive electrode sheet as described in claim 9.